Rancang Bangun Model Sistem Rantai Pasok Agroindustri Limbah Cerutu yang Berkelanjutan Pada CV Dwipa Nusantara Tobacco Jember - Wahyono, Nanang Dwi; Kurniawati, Dewi; Harkat, Avisenna; Edwinsyah Yanuan Putra, Mohammad; Eka Ardhi Pratama, Fredy; Wahyu Winadi Atmajaya, Aditya (Jurnal Ilmiah Inovasi, 2024)
This research develops a sustainable supply chain system model for the cigar waste agroindustry at CV Dwipa Nusantara Tobacco, Jember, using the Interpretative Structural Modelling (ISM) approach. Cigar waste, previously considered valueless, is processed into diversified products that have the potential to enhance the company's economic value. The designed model aims to address inefficiencies in the supply chain that prevent optimal utilization of waste. ISM identifies key elements in the supply chain, such as raw material supply, labor, and processing technology. The study analyzes the export supply chain of cigar waste at CV Dwipa Nusantara Tobacco Jember. Three main elements are identified: needs, barriers, and institutions, each with interrelated sub-elements. Using the Reachability Matrix (RM), relationships among sub-elements are examined using transitivity rules. The results reveal sub-elements that act as key drivers, particularly in raw material availability, production technology, and export regulations. These findings are expected to enhance supply chain efficiency and improve product competitiveness in international markets.